Management Based on Multimodal Brain Monitoring May Improve Functional Connectivity and Post-operative Neurocognition in Elderly Patients Undergoing Spinal Surgery - Yang, Shuyi; Xiao, Wei; Wu, Hao; Liu, Yang; Feng, Shuai; Lu, Jie; Wang, Tianlong (Frontiers in Aging Neuroscience, 2021)
Perioperative neurocognitive disorder (PND) is a common condition in elderly patients undergoing surgery. Sedation, analgesia, regional cerebral oxygen saturation (rSO2), and body temperature are known to be associated with PND, but few studies have examined the contribution of these factors combined in detail. This prospective, randomized, controlled, double-blinded study investigated whether anesthesia management based on multi-modal brain monitoring—an anesthesia management algorithm designed by our group—could improve postoperative cognitive function and brain functional connectivity (FC) in elderly patients undergoing elective spinal surgery with general anesthesia. The patients (aged ≥65 years) were randomized into 2 groups (control [Group C], n=12 and intervention [Group I], n=14). Patients in Group I were managed with multi-modal brain monitoring (patient state index, spectral edge frequency, analgesia nociception index, rSO2, and temperature) and those in Group C were managed with routine anesthesia management. All patients were pre- and postoperatively evaluated (7 days after surgery) with the Montreal Cognitive Assessment (MoCA). Amplitude of low frequency fluctuation (ALFF) and FC were analyzed after resting-state functional magnetic resonance imaging. Serum C-reactive protein (CRP) and lipopolysaccharide levels were measured and the correlation between FC and changes in inflammatory marker levels were analyzed. Mean postoperative MoCA score was higher in Group I (24.80±2.09) than in Group C (22.56±2.24) (P=0.04), with no difference in PND incidence between groups (28.57% vs 16.67%; P=0.47). Group I also showed significantly increased ALFF values in several brain regions after surgery (P<0.05) and FC between the left hippocampus and left orbital inferior frontal gyrus, left middle frontal gyrus, left superior temporal gyrus, and left precentral gyrus was enhanced (P<0.05), which was negatively correlated with the change in serum CRP (pre vs post intervention) (R=−0.58, P=0.01). These results suggest that management of elderly patients undergoing surgery by multi-modal brain monitoring may improve postoperative neurocognition and FC by reducing systemic inflammation.